1993
DOI: 10.1128/aac.37.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibitory action of the gastric proton pump inhibitor lansoprazole against urease activity of Helicobacter pylori: unique action selective for H. pylori cells

Abstract: The gastric proton pump inhibitor lansoprazole, its active analog AG-2000, and omeprazole dose dependently inhibited urease activity extracted with distilled water from Helicobacterpylori cells; the 50%1 inhibitory concentrations were between 3.6 and 9.5 ,M, which were more potent than those of urease inhibitors, such as acetohydroxamic acid, hydroxyurea, and thiourea. These compounds also inhibited urease activity in intact cells of H. pylori and Helicobacter mustelae but did not inhibit ureases from other ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 39 publications
1
99
1
Order By: Relevance
“…Indeed, the current study clearly implicates CD46 as inhibitor of urease activity, and earlier findings by Nagata et al (1993) 38 suggested that inhibition of urease activity is lethal to H. pylori. In addition to UreA, the affinity columns and mass spectrometry also identified AhpC.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Indeed, the current study clearly implicates CD46 as inhibitor of urease activity, and earlier findings by Nagata et al (1993) 38 suggested that inhibition of urease activity is lethal to H. pylori. In addition to UreA, the affinity columns and mass spectrometry also identified AhpC.…”
Section: Discussionsupporting
confidence: 72%
“…Urease activity assay. The method to measure urease activity has previously been described 38 . Briefly, bacteria at 10 8 CFU/ml were centrifuged, washed and resuspended with ice-cold de-gassed 20 mM sodium phosphate (pH 6.8).…”
Section: Generation Of H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…These inhibitors generally divided into two classes, substrate structural analogs like hydroxamic acid (Kobashi K 1962,;Krajewska B 2009;Muri EMF 2003) and those which affect the mechanism of the reaction like phosphoramidat (Amtul Z 2002;Kot M 2001). Lansoprazole (Nagata K 1993), omeprazole (Kuehler TC 1995), thiol-compounds (Todd MJ 1989), quinines (Bundy LG 1973) and schiff base derivatives (Hanif M 2012) are reported as potent urease inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Thiourea and its derivatives cannot be hydrolyzed by ureases of different origin 16,17 or they are inhibitors of these enzymes. 18 Therefore, the permanently bonded drug conjugates containing a thiourea-linking moiety are expected as stable molecules under biological conditions. Consequently, the prepared permanently bonded drug conjugates do not correspond to a delivery system, but represent original macromolecules carrying bioactive endgroups.…”
mentioning
confidence: 99%